2020
DOI: 10.1002/cne.25089
|View full text |Cite
|
Sign up to set email alerts
|

Age, sex, and regional differences in scavenger receptor CD36 in the mouse brain: Potential relevance to cerebral amyloid angiopathy and Alzheimer's disease

Abstract: Scavenger receptor CD36 contributes significantly to lipid homeostasis, inflammation, and amyloid deposition, while CD36 deficiency is associated with restored cerebrovascular function in an Alzheimer's disease (AD) mouse model. Yet the distribution of CD36 has not been examined in the brain. Here, we characterized CD36 gene and protein expression in the brains of young, middle aged, aged, and elderly male and female C57BL/6J mice. Age‐related increases in CD36 mRNA expression were observed in the male hippoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…In AD, the dysregulation of scavenger receptor activity has been implicated in the clearance of Aβ plaques, which are one of the hallmark pathological features of the disease 34 . Previous studies have reported sex differences in scavenger receptor expression in the context of AD 35 . Additionally, we observed differences in GSEA enrichment of neurogenesis pathways in Microglia under AD conditions.…”
Section: Resultsmentioning
confidence: 92%
“…In AD, the dysregulation of scavenger receptor activity has been implicated in the clearance of Aβ plaques, which are one of the hallmark pathological features of the disease 34 . Previous studies have reported sex differences in scavenger receptor expression in the context of AD 35 . Additionally, we observed differences in GSEA enrichment of neurogenesis pathways in Microglia under AD conditions.…”
Section: Resultsmentioning
confidence: 92%
“…Indeed, this hypothesis agrees with the lower retinolemia in females and could be due to either a lower hepatic expression of its transporter protein, i.e., RBP4, [37] leading to a lower plasma concentration of VA, or to a difference in expression of Cd36 between males and females. [45] Indeed, it has been shown that this protein plays a role in the mobilization of hepatic VA stores, since Cd36 -/mice accumulated higher hepatic VA stores than wild type mice. [46] The last parameter of hepatic metabolism of VA that was affected by the sex of animals was the relative proportions of each retinyl ester species.…”
Section: Discussionmentioning
confidence: 99%
“…To provide comprehensive, visual representations, spatial mappings were created with Adobe Photoshop 2023. These mappings, presented as a six-color gradient scale, encompass eight brain atlas sections [50]. The sections were adapted from the Allen Mouse Brain Atlas (Allen Institute of Brain Science, 2011) and Paxinos and Franklin’s “The Mouse Brain in Stereotaxic Coordinates,” Fifth Edition [50].…”
Section: Methodsmentioning
confidence: 99%
“…Regional immunoreactivity strength score for JNK3. Eight matching sections were selected from each animal and subjected to immunohistochemical staining for JNK3 (DAB) as described previously [50]. Utilizing a BZ-X All-in-One microscope (Keyence, Itasca, IL), a single observer scored the immunoreactivity strength to JNK3.…”
Section: Immunofluorescent (If)mentioning
confidence: 99%